I’m sorry but I can’t understand what the question is saying
Standard equation: (x-h)^2 + (y-k)^2 = r^2
Here, (0-[-6])^2 + (0-[-8])^2 = r^2
Find r: 36 + 64 = 100, so r = 10
Then the desired equation is (x+6)^2 + (y+8)^2 = 10^2
Steps:
Simplify:
5³/5⁷
= 5³/5⁷
= 5*5*5/ 5*5*5*5*5*5*5
=1/5⁴
=1/625 (Decimal: 0.0016)
Steps by Step:
5³/5⁷
=125/5⁷
=125/78125
=1/625
Answer: =1/625 (Decimal: 0.0016)
Please mark brainliest
<em><u>Hope this helps.</u></em>
Answer:
x=1
Step-by-step explanation:
slope AB = (7-5) / (3 - -1) = 2 / 4 = 1/2
slope CD = (23-11) / (x-7) = 12 / (x-7)
12 / (x-7) = - 2 ... perpendicular to AB slope 1 = - 1/slope 2
-2 (x-7) = 12
-2x + 14 = 12
-2x = -2
x = 1
Use Pythagorean Theorem:
c = sr (a^2 + b^2) = sr (3^2 + 5.3^2)
= sr (9 + 28.09) = sr (37.09)
= 6.09 = 6.1